2017
DOI: 10.1089/ars.2016.6844
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal MicroRNA-15a Transfer from the Pancreas Augments Diabetic Complications by Inducing Oxidative Stress

Abstract: Our findings suggest that circulating miR-15a contributes to the pathogenesis of diabetes and supports the concept that miRNAs released by one cell type can travel through the circulation and play a role in disease progression via their transfer to different cell types, inducing oxidative stress and cell injury. Antioxid. Redox Signal. 27, 913-930.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(81 citation statements)
references
References 52 publications
2
72
0
Order By: Relevance
“…The upregulated levels of miR‐15a were linked to disease pathogenesis via the upregulation of oxidative stress. The results of these studies indicated that miRNA‐containing exosomes could have significant impact on the pathogenesis and progression of diabetic disease . To assess the value of exosome miRNAs as biomarkers in diabetes, one group examined the miRNA expression in plasma‐derived exosomes.…”
Section: Role Of Exosomesmentioning
confidence: 99%
“…The upregulated levels of miR‐15a were linked to disease pathogenesis via the upregulation of oxidative stress. The results of these studies indicated that miRNA‐containing exosomes could have significant impact on the pathogenesis and progression of diabetic disease . To assess the value of exosome miRNAs as biomarkers in diabetes, one group examined the miRNA expression in plasma‐derived exosomes.…”
Section: Role Of Exosomesmentioning
confidence: 99%
“…MiR‐15a , a miRNA that plays an important role in insulin production in pancreatic β‐cells, is increased in the plasma of diabetic patients. Pancreatic miR‐15a can enter the bloodstream inside exosomes and may contribute to retinal injury and oxidative stress by targeting AKT3 in retinal cells . Another recent report showed that the exosome fraction isolated from mouse plasma was enriched in immunoglobulins (Igs) associated with the vesicles .…”
Section: Exosomes and Evs In Diabetesmentioning
confidence: 99%
“…In addition, Yin et al have showed that miR-214 secreted by tumor cells can enter CD4+ T cells, repressing local expression of PTEN and thus affecting Treg proliferation [37]. Another group suggests that miR-15a, produced in pancreatic β-cells, can enter the bloodstream and contribute to retinal injury [38]. The way of such intercellular miRNA-mRNA regulation has been found in a wide range of biological processes [10].…”
Section: Functions Of Secreted Micrornasmentioning
confidence: 99%